LENGTH-WEIGHT RELATIONSHIP AND RELATIVE CONDITION FACTOR OF THE SCALY HAIRFIN ANCHOVY, SETIPINNA TATY (VALENCIENNES, 1848), FROM THE HOOGHLY-MATLAH ESTUARINE SYSTEM OF WEST BENGAL, INDIA - MONDAL, ANWESHA; ZIAUDDIN, GOLAM; NAGESH, TALAGUNDASRINIVASAN; DAS, SUDHIR KUMAR; JANA, SUSMITA; BHAKTA, DIBAKAR (Journal of the Inland Fisheries Society of India, 2025)
The length-weight relationships (LWRs) of Setipinna taty (Valenciennes, 1848) from the Hooghly-Matlah estuarine system of West Bengal were estimated. The study is based on 447 samples (154 males and 293 females) collected at monthly intervals for a period of 1 year (February 2022 to January 2023). There is no significant difference (p>0.01) in growth rate for both sexes. The b values were estimated at 2.489, 2.88, and 2.716, with r2 values of 0.798, 0.815, and 0.814 for males, females, and pooled samples, respectively. The growth pattern was found to be negatively allometric. The month-wise mean Kn values were found during the monsoon (1.003±0.006), and post-monsoon (1.006±0.004) for combined samples. In males, the average Kn value is highest in post-monsoon (1.003±0.003) and lowest in pre- monsoon (0.983±0.0471). Females have the highest Kn value during the monsoon (1.003±0.001) and the lowest during the pre-monsoon (0.972±0.064). The lengthwise estimated mean Kn values varied from 0.91 to 1.03, indicating the moderately good condition of the fish in the study area. The results can be used for sustainable management and conservation of this commercially important species in the studied estuary.